Blast-induced damage : a summary of SveBeFo investigations - Saiang, David (Luleå tekniska universitet, Geoteknologi, 2008)
This report presents a summary of the blast damage investigation carried out by SveBeFo (Swedish Rock Engineering Research) during the period 1991 to 2003 at various hard rock sites in Sweden. The objective of this report is to present a synopsis of the important factors that influence the development and extent of the blast-induced damage zone, nature and characteristics of blast-induced fractures, and a summary of the blast-damage thickness with reference to the existing perimeter blasting damage guidelines for tunnelling and drifting practices in Sweden. Ultimately this report will assist the author in developing numerical models to study the effects of blast-induced damaged zone on stability parameters. It has to be stated clearly that this report is intended as summary and not a reproduction of the works of SveBeFo. It may not also represent the actual conclusions or views of SveBeFo in areas where this author attempted to interpret and conclude from some of the data. Interested readers are strongly urged to consult the SveBeFo publications referenced in this report.The SveBeFo blast damage investigations during the period 1991 to 2003 were carried out at three principle hard rock sites: (i) Vånga granite quarry, (ii) LKAB's Malmberget and Kiruna mines and (iii) SKB's TASQ tunnel. The primary goal of these studies was to improve perimeter blasting guidelines for tunnelling and drifting in hard rock masses in Sweden. Within this scope were several objectives such as: (i) to develop guidelines for blast-induced damage control for drifting and tunnelling in hard rock masses, (ii) devise method for blast damage assessment, (iii) verification of the devised methods in tunnelling and drifting sites. Generally used perimeter blasting techniques, particularly smooth blasting, were employed in the tests. Multiple holes of different, but commonly used, diameters for perimeter holes were used. The explosives used were those commonly used for tunnelling and drifting. After the blasts saw cuts were extracted from the ...